PERANCANGAN SISTEM INFORMASI JURUSAN TEKNOLOGI REKAYASA KOMPUTER JARINGAN (TRKJ) PADA POLITEKNIK SAINT PAUL SORONG BERBASIS WEBSITE - Delta Sari Lobo; Marcelinus Petrus Saptono; Raditya Faisal Waliulu; Ery Murniyasih (Electro Luceat, 2023)
Saint Paul Sorong Polytechnic is one of the universities in Sorong City, which consists of several departments and also does not have a website as a means to provide official information from each department, one of which is the Department of Computer Network Engineering Technology. So the purpose of this research is that the department's information system can be displayed through the official website and make it easier for students to register for KKN-PPM & Job Training. The purpose of this research is to facilitate data processing for the TRKJ department, to facilitate students who will register for KKN-PPM & Job Training, to produce a website that can function as a medium of information and communication that is more effective and efficient. This research method uses the System Development Life Cycle (SDLC) or the system development life cycle is the process used by systems analysts to develop information systems, starting from planning, determining requirements, and designing. The results of the black box testing are a web-based Computer Network Engineering Technology Information System in accordance with what is expected in this study, it can be seen from the system according to what is produced from the system being tested, such as inputting, deleting, and editing data in the system, performing KKN-PPM registration and practical work as expected, namely being able to print proof of registration and upload reports.